Analysis of Railway Service Levels Due to Double Track Construction at Sepanjang-Mojokerto Segment - Estikhamah, Fithri; Zainab, Siti; Wardhani, Primasari Cahya; Utomo, Nugroho; Solin, Dian Purnamawati (Nusantara Science and Technology Proceedings, 2023)
Railways in Indonesia still show problems, such as time delays. To make train services in Indonesia better, government efforts are needed, one of which is the development of new infrastructure, such as the construction of a double-track train such as Sepanjang to Mojokerto segment. So it is necessary to analyze the level of service both in existing conditions and after construction. The analysis was carried out in two conditions, namely, full single track and full double track. For full double-track reference, a simulation is carried out with an auxiliary program, namely the Railway Operation Simulator (ROS). By entering data in the form of station layouts, train facilities, and signaling systems and blocks. Based on the analysis results, it shows that the double track in the Sepanjang-Mojokerto segment affects the level of service. The prediction of service levels for the Sepanjang-Mojokerto segment shows that three road plots have LoS A. So, overall, with the construction of the double track, this segment is operating below capacity and has low traffic.